PERSEPSI DAN SIKAP PARA PIHAK TERHADAP LANSKAP BERHUTAN DI KOTA PAGARALAM, DAS MUSI HULU SUMATERA SELATAN - Edwin Martin; Bambang Tejo Premono; Ari Nurlia (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2013)
Problems of deforestation in the upstream watershed site can not be stopped or slowed down by current policies and programs, therefore other approaches are still required in accordance with the dynamics of socioeconomics condition of local communities. This study was intended to answer questions about how to start a forest landscape management in upland areas, through case study in the Pagaralam, South Sumatra. Researchis done by a survey of stakeholders who have interests and power on the forested landscape in Pagaralam. Data were analyzed with nonparametric statistics, and then discussed with the parties through FGD. The results showed that the actors in the goverment and land users have different perceptions and attitudes in assesing forested landscape. In addition to the importance of awareness-raising for land users through the media that raise enviromental issues, program priorities to initiate the management of forest landscapes in the upper basin include replanting and protecting springs and along side of the river.